UI/UX DESIGN OF THE HOUSET WEBSITE AS A MARKETPLACE AND ROOM VISUALIZATION MEDIA - Ghaisani, Julia; Komariah, Siti Hajar; Aulia, Rahmiati (eProceedings of Art & Design, 2023)
PT. Houset Hunian Estetika is a startup engaged in interior design and furniture that makes it easy for the public to visualize the room and apply the room according to the desired interior design and sell furniture online. The way Houset makes it easy is by providing an interior design canvas in a 3D model so as to provide an experience for users in  choosing  the  desired  interior  design  and  furniture. Houset  also  sells  furniture  that matches the interior design shown in 3D models. However, there is no media platform in the form of a website. With this phenomenon, the authors intend to build a platform for PT. Houset Hunian Estetika through the UI/UX design of the Houset website which  is a means  of marketplace  and  room  visualization media.  This  research  and  design  uses qualitative methods  as  data  collection  with  a  literature  study  approach,  observation, interviews, questionnaires, matrix analysis and SWOT analysis. The design of this website is  expected  to make  it  easier  for  people  to  get  furniture while  helping  to  get  a  visual picture  of  the  room  in matching  the  interior design  that  is  suitable  for  the  room and helping its arrangement. Keywords:  interior  design,  marketplace,  PT.  Houset  Hunian  Estetika,  UI/UX,  website design